Fast EXAFS in synchronous scanning mode at PETRA P06. (May 2016) - Chernikov, Roman; Welter, Edmund; Caliebe, Wolfgang; Wellenreuther, Gerd; Falkenberg, Gerald
Abstract: First fast EXAFS spectra have been successfully measured at the Hard X-ray Micro-probe Beamline P06 (PETRA III) synchronously scanning the U32 undulator gap and the monochromator Bragg axis. Stability and spatial homogeneity of the beam are proved to be the limiting factors for the quality of the EXAFS spectra, whereas the performance of the data acquisition electronics limits the energy resolution when total scan time is reduced to 30 seconds. Results of the test measurements give us the estimate of the utmost performance of 510 seconds per full EXAFS scan considering certain hardware modifications.